Opportunities and challenges of asynchronous video interviews: Perceptions of human resources professionals from Türkiye - Ümit Deniz İlhan; Burcu Kümbül Güler; Dilara Turgut; Cem Duran (PLoS ONE, 2025)
In the context of global technological advancements, asynchronous video interviews (AVIs) have emerged as an innovative tool in recruitment, offering potential to transform traditional hiring practices. This study aims to enhance understanding of the opportunities and challenges associated with AVIs in recruitment processes by examining the perspectives of human resources (HR) professionals in Türkiye. A qualitative research methodology with a phenomenological approach was employed. 15 HR professionals experienced in asynchronous video interviewing from diverse organizations participated in online, open-ended, semi-structured, in-depth interviews. The collected data were analyzed through thematic analysis using MAXQDA 2024. Findings indicated that AVIs offer significant opportunities, such as improving process efficiency, enhancing candidate experience, promoting fairness and inclusivity, and supporting organizational goals. However, the study identified critical challenges, including diminishing candidate experience, undermining fairness and increasing deceptive impression management, reducing job satisfaction among HR professionals, and imposing operational and financial constraints. As one of the first studies to explore HR professionals’ perceptions of AVIs in Türkiye, this study provides valuable insights into their adoption in developing economies and highlights the broader implications of AVIs in the global recruitment practices. The findings emphasize the need for tailored strategies to maximize benefits, address challenges, and balance the needs of both candidates and HR professionals.